2021
DOI: 10.3233/jad-210050
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Outcomes of Patients with Dementia Compared to an Aging Cohort Hospitalized During the Initial New York City COVID-19 Wave

Abstract: Background: Patients with dementia are vulnerable during the coronavirus disease 2019 (COVID-19) pandemic, yet few studies describe their hospital course and outcomes. Objective: To describe and compare the hospital course for COVID-19 patients with dementia to an aging cohort without dementia in a large New York City academic medical center. Methods: This was a single-center retrospective cohort study describing all consecutive patients age 65 or older with confirmed COVID-19 who presented to the emergency de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 26 publications
3
18
0
1
Order By: Relevance
“…Quantifying the burden of neurological events during the acute phase of illness will shed light on potential risk factors and mechanisms of post-COVID-19 neuropsychiatric conditions increasingly reported in survivors. 2,[21][22][23][24] Several questions remain with regards to the implications of the timing and severity of neurological manifestations on post-acute COVID-19 recovery. Well-designed cohorts in the acute COVID-19 period are needed to define risk factors associated with poor outcomes in the post hospitalization period, especially amongst multiethnic cohorts who were impacted significantly by the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Quantifying the burden of neurological events during the acute phase of illness will shed light on potential risk factors and mechanisms of post-COVID-19 neuropsychiatric conditions increasingly reported in survivors. 2,[21][22][23][24] Several questions remain with regards to the implications of the timing and severity of neurological manifestations on post-acute COVID-19 recovery. Well-designed cohorts in the acute COVID-19 period are needed to define risk factors associated with poor outcomes in the post hospitalization period, especially amongst multiethnic cohorts who were impacted significantly by the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“… 7 We expect that residents with ADRD generally present with less specific symptoms of COVID‐19 than those without ADRD. 2 , 3 , 4 This could obscure clinical detection and delay diagnosis, resulting in potential exposure of more staff and residents to SARS‐CoV‐2. Our findings demonstrate the critical importance of infection control and underscore the importance of viral testing and vital signs monitoring, especially in facilities with high ADRD prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…1 Retrospective studies of hospitalized older adults with COVID‐19 and Alzheimer's disease and related dementias (ADRD) report alterations in cognition or functional status as the most common symptoms. 2 , 3 , 4 Furthermore, ADRD reduces adherence to infection control measures in NH such as testing, masking and physical distancing. 5 , 6 , 7 Through these multiple mechanisms, the contextual factor of ADRD prevalence could lead to increased risk of SARS‐CoV‐2 in a NH.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has presented another challenge to individuals living with dementia and their families as the disease has a disproportionate burden on this group of patients. Multiple studies have shown that, despite attempts to control for other health conditions, dementia is associated with a higher risk of SARS-CoV-2 infection and mortality after COVID-19 disease [38][39][40][41]. One study of community dwelling older adults in the United Kingdom found that neurodegenerative diseases were more strongly associated with COVID-19-related death than the other health conditions and demographic variables they tracked.…”
Section: Prognostication and Hospice Referralmentioning
confidence: 99%